Evaluation of Health Related Quality of Life in Sub-acute Stroke Subjects using Stroke Impact Scale - A Descriptive Study. - Lakhotia, Sonia; Sarma, Somyata Satpathy; Kakati, Trishna; Medhi, Himashree (Indian Journal of Physiotherapy & Occupational Therapy)
Background: Healthrelated quality of life (HRQoL) is becoming important to measure as it is an indication of an outcome after stroke. Stroke Impact scale can be used as a stroke outcome measure that aims to effectively assess the various domains important in determining HRQoL in sub-acute stroke subjects. Aim: The purpose of this study was to assess the HRQoL in sub-acute stroke subjects using Stroke Impact Scale (SIS) version 3.0 and to estimate the impact of individual characteristics such as age, duration of stroke, co-morbidities and clinical correlates such as cognitive level, functional level and severity on HRQoL in sub-acute stroke subjects. Materials & Methodology: A total of fifty subjects after eight to thirty days poststroke onset participated in this study. They were evaluated for eligibility using Mini Mental State Examination (MMSE) and Modified Barthel Index (MBI). After history taking, the severity of stroke was assessed using the National Institute of Health Stroke Scale (NIHSS) and the HRQoL was assessed using SIS questionnaire with eight domains: strength, hand function, mobility, physical and instrumental activities of daily living, memory and thinking, communication, emotion and social participation. Results: There was poor HRQoL in areas of hand function, mobility, social participation and stroke recovery with the highest areas in memory and communication. SIS domains: Strength, mobility, emotion, communication, participation and recovery negatively correlated with co-morbidity whereas only memory positively correlated with MMSE. Conclusion: The study emphasizes the impact of and the need to take demographic and personal characteristics including age, duration of stroke and co morbidities into account in the planning of post stroke rehabilitation programs. SIS is an important stroke outcome measure that can be used effectively to assess the various domains important in determining HRQoL in stroke subjects.